2002
DOI: 10.1182/blood-2002-01-0055
|View full text |Cite
|
Sign up to set email alerts
|

Anti-μ-opioid-receptor IgG antibodies are commonly present in serum from healthy blood donors: evidence for a role in apoptotic immune cell death

Abstract: We previously observed the presence of anti-human -opioid-receptor (anti-hMOR) autoantibodies in IgG pools prepared from several thousand healthy blood donors. These autoantibodies behaved agonistically because of their ability to bind to the first and third extracellular loops of the receptor. In this study, we found that each healthy donor's serum contained antihMOR IgG autoantibodies with a specific activity against both the first and the third extracellular loops of the receptor. Because of the inability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Some of these immunomodulatory effects are dependent on stimulation of MOR in situ (Yin et al, 2000;Mace et al, 2002;Wang et al, 2002a, b). However, as exemplified in the T cell response to mitogens, the inhibitory effect of morphine is dependent on the tissue context.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of these immunomodulatory effects are dependent on stimulation of MOR in situ (Yin et al, 2000;Mace et al, 2002;Wang et al, 2002a, b). However, as exemplified in the T cell response to mitogens, the inhibitory effect of morphine is dependent on the tissue context.…”
Section: Discussionmentioning
confidence: 95%
“…The MOR mRNA undetectable in resting T lymphocytes and found in some activating conditions, is upregulated within an interleukin (IL)-4-or tumor necrosis factor-alpha-rich microenvironment (Gavériaux et al, 1995;Kraus et al, 2001Kraus et al, , 2003aMadden et al, 2001;Jaume et al, 2007;Borner et al, 2008). It is noteworthy that most of the immunosuppressive effects of morphine or stress-induced endogenous opioid release, such as apoptosis of spleen cells, reduction of both inflammation and natural killer cell activity, are mediated through MOR activation in mice (Shavit et al, 1984;Gavériaux-Ruff et al, 1998;Yin et al, 1999Yin et al, , 2000Mace et al, 2002;Wang et al, 2002a, b;Philippe et al, 2003). As a matter of fact, although DOR and enkephalins are together expressed in both CD4 þ T lymphocytes and antigen-presenting mature DCs, opioid receptor neutralization altered neither the antigen-induced proliferation of lymphocytes nor their sensitivity to apoptosis in vivo (Jaume et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Following reports of the presence of anti-MOR antibodies in the serum of healthy individuals (Mace et al, 1999b, Mace et al, 1999a, Mace et al, 2002), we focused upon autoantibody activity to DOR, a receptor shown to be expressed on peripheral blood cells, including T and B lymphocytes (Miller, 1996, Nguyen and Miller, 2002, Sharp, 2004, Sharp et al, 2001, Shen et al, 2005). Various groups have shown that the first and the third extracellular loops of the opioid receptors are critical for ligand binding specificity and functional activation of the receptor (Dietrich et al, 1998, Fadhil et al, 2004, Li et al, 1996, Mace et al., 1999b, Varga et al, 1996, Varga et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the expression of the opioid receptors on immune cells, another piece of evidence that supports the bidirectional network of communication between the opiate and immune system is the discovery that IgG autoantibodies directed against the human MOR are commonly present in the serum of healthy individuals (Mace et al, 1999a, Mace et al, 2002). These autoantibodies display an agonistic activity, demonstrated by the inhibition of forskolin stimulated cAMP accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation